2021
DOI: 10.3389/fcell.2021.661472
|View full text |Cite
|
Sign up to set email alerts
|

Organoids of the Female Reproductive Tract: Innovative Tools to Study Desired to Unwelcome Processes

Abstract: The pelviperineal organs of the female reproductive tract form an essential cornerstone of human procreation. The system comprises the ectodermal external genitalia, the Müllerian upper-vaginal, cervical, endometrial and oviductal derivatives, and the endodermal ovaries. Each of these organs presents with a unique course of biological development as well as of malignant degeneration. For many decades, various preclinical in vitro models have been employed to study female reproductive organ (patho-)biology, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 165 publications
(224 reference statements)
1
26
0
Order By: Relevance
“…Numerous studies have featured the generation of organoids derived from primary tissues or hPSCs, such as the ovaries, fallopian tubes, endometrium, and cervix. Organoids can also be generated from disorders of the FRS such as endometriosis and cancer [ 86 ].…”
Section: Bmps Signaling In Female Reproductive Systemmentioning
confidence: 99%
“…Numerous studies have featured the generation of organoids derived from primary tissues or hPSCs, such as the ovaries, fallopian tubes, endometrium, and cervix. Organoids can also be generated from disorders of the FRS such as endometriosis and cancer [ 86 ].…”
Section: Bmps Signaling In Female Reproductive Systemmentioning
confidence: 99%
“…Studies in cultured stromal cells are one key model, as they are amenable to mechanistic studies; however, in vitro models in which to study epithelial cells have proven challenging. Recently, however, innovative organoid culture systems have been developed that provide a platform to study processes intrinsic to endometrial epithelial cells [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these studies, it can be mentioned to the successful 3D cervical organoids from ecto-and endocervical epithelial cells (Maru et al, 2019(Maru et al, , 2020. Although studies in this area are very limited, but promising results have been reported by researchers (Heremans et al, 2021).…”
Section: Cervical Organoidmentioning
confidence: 99%